ANALISIS PERBEDAAN KINERJA KARYAWAN PADA PT SURYA INDAH FOOD MULTIRASA JOMBANG - Lailatus Sa’adah; Linda Martadani; Ahmad Taqiyuddin (Jurnal Inovasi Penelitian, 2021)
The purpose of this study was to analyze the difference of employee performace in PT Surya Indah Food Multirasa Jombang districts. This type of research is quantitative research with survey research methods. In collecting data using purposive sampling techniques. The population of this research is all employees at PT Surya Indah Food Multirasa Jombang districts, so that the sample in this study is 52 respondents. To analyze the data obtained using the Classic Assumption Test, and One Way Anova. Whereas the data collection was carried out through several techniques, namely field studies and lift deployment studies. The results of research and data processing show that the three independent variables, gender, age, and length of working simultaneously have a significant effect on employee performance. Correlation coefficient test results show that the R value of 0,662, it means gender, age, and legth of working together have a very strong relationship of employee performance. While the result of One Way Anova test show that sig is 0,009 < 0,05 that it can be interpreted there is a performance difference of gender, than sig as 0,011 < 0,05 that it can be interpreted there is a performance difference of age, and than sig as 210 > 0,05 that it can be interpreted there is a performance difference oflegth of working. Expected things to pay attention to further improve employee performance at PT Surya Indah Food Multirasa Jombang districts that is evaluating in the employee’s work